2003
DOI: 10.1097/01.brs.0000048508.72515.ec
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Spinal Cord Injury Without Radiographic Abnormality in a Skeletally Mature Patient

Abstract: A rare case of thoracic spinal cord injury without radiographic abnormality manifested as a result of traction injury to the sciatic nerves caused by bilateral violent lower limb injuries in a skeletally mature patient is presented. To the best of the authors' knowledge, such a case has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Thin section and high magnetic field MRI examinations can reveal lesions that cannot be monitored with routine MRI scans [13]. Samsani et al [14] believed that after spinal injury, paravertebral venous plexus was abnormal, veins were tortuous and irritated, and paravertebral venous backflow was stagnant, which explained that the SCI segment was higher than the compression segment shown in MRI. The hemodynamics of SCI suggested that compressions could cause spinal cord vascular obstruction and thus alter the hemodynamics of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Thin section and high magnetic field MRI examinations can reveal lesions that cannot be monitored with routine MRI scans [13]. Samsani et al [14] believed that after spinal injury, paravertebral venous plexus was abnormal, veins were tortuous and irritated, and paravertebral venous backflow was stagnant, which explained that the SCI segment was higher than the compression segment shown in MRI. The hemodynamics of SCI suggested that compressions could cause spinal cord vascular obstruction and thus alter the hemodynamics of the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases of thoracic SCIWORA in adult patients have been reported at T4 and above 3 4. One case report describes SCIWORA at T10 in a severely poly-traumatised patient but following significant high energy lower limb injuries 2. The authors proposed that sudden bilateral traction on the sciatic nerves accounted for the observed cord injury in this particular case.…”
Section: Discussionmentioning
confidence: 82%
“…Spinal cord injury without radiographic abnormality (previously known as SCIWORA) is exceedingly rare in skeletally mature individuals, with very few previous case-reports,24 most of which occurred in the context of high energy polytrauma. To our knowledge, this is the first reported case occurring in the lower thoracic spine as an isolated injury following a low-energy mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Samsani et al reported a case of thoracic spinal cord injury without radiographic abnormality in a skeletally mature patient, and associated spinal ligamentous injuries were excluded by MRI [6]. CT is recommended because it demonstrates thoracic OLF distribution patterns.…”
Section: Discussionmentioning
confidence: 97%